2010
DOI: 10.1103/physrevlett.105.034501
|View full text |Cite
|
Sign up to set email alerts
|

Stokes’s Cradle: Newton’s Cradle with Liquid Coating

Abstract: Flows involving liquid-coated grains are ubiquitous in nature (pollen capture, avalanches) and industry (air filtration, smoke-particle agglomeration, pharmaceutical mixing). In this work, three-body collisions between liquid-coated spheres are investigated experimentally using a "Stokes' cradle", which resembles the popular desktop toy known as the Newton's cradle. Surprisingly, previous work indicates that every possible outcome was observed in the wetted system except the traditional Newton's cradle (NC) ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…However, we found the inclusion of string tension critical to predicting the correct outcomes and trends since the particles rotate through a significant angle before deagglomerating, allowing for large string tension forces to act over a long period of time. Finally, based on recent experimental evidence [10], we do not presume cavitation upon rebound precludes resistance and instead include the effect of fluid resistance.…”
Section: Theory Descriptionmentioning
confidence: 99%
“…However, we found the inclusion of string tension critical to predicting the correct outcomes and trends since the particles rotate through a significant angle before deagglomerating, allowing for large string tension forces to act over a long period of time. Finally, based on recent experimental evidence [10], we do not presume cavitation upon rebound precludes resistance and instead include the effect of fluid resistance.…”
Section: Theory Descriptionmentioning
confidence: 99%
“…Antonyuk et al [24] demonstrated that the energy loss caused by the viscous damping force and drag force are more significant than other factors in the energy dissipation process. Recently, the Hrenya group from Colorado University has undertaken much work to characterize the collision mechanics in the presence of liquid: Donahue et al [25,26] developed a scaling theory to characterize the three-body collision that considers liquid bridge force existing between agglomerating particles initially and pressure dependence in the liquid viscosity. In another paper, they explored particle-particle oblique collisions and observed a rotating doublet for two obliquely colliding particles before deagglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…For normal collisions, de-agglomeration or rebound of colliding particles occurs for values of St n greater than a critical Stokes number, namely St * n . The value of St * n can be determined either empirically via experiments or theoretically by considering the properties of both the fluid and the solid particles (Ennis, Tardos & Pfeffer 1991;Davis, Rager & Good 2002;Donahue, Hrenya & Davis 2010a). Recent experiments on normal collisions between a particle and a wetted wall have verified the lubrication force for St n < St * n (Marston, Wong & Thoroddsen 2010).…”
mentioning
confidence: 96%